2011
DOI: 10.1097/aln.0b013e318218119d
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with Epinephrine (Adrenaline) in Suspected Anaphylaxis during Anesthesia in Denmark

Abstract: Background: Literature on the use of epinephrine in the treatment of anaphylaxis during anesthesia is very limited. The objective of this study was to investigate how often epinephrine is used in the treatment of suspected anaphylaxis during anesthesia in Denmark and whether timing of treatment is important. Methods: A retrospective study of 270 patients investigated at the Danish Anaesthesia Allergy Centre after referral due to suspected anaphylaxis during anesthesia was performed. Reactions had been graded b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 36 publications
2
29
0
2
Order By: Relevance
“…40 One study demonstrated that significant delays in treatment with epinephrine occurred in about one-third of cases in Denmark. 41 Per case mortality was estimated to be one in 26.6 cases in the UK for all causative drugs, 40 an outcome very similar to that observed in France for mortality related to NMBA anaphylaxis, 39 and that reported for all causative drugs in the US 42 and Japan. 27 A perioperative anaphylaxis mortality rate of 0e1.4% was recently reported for Western Australia (2000e2009).…”
Section: Incidence Causal Agents and Mortalitysupporting
confidence: 64%
See 1 more Smart Citation
“…40 One study demonstrated that significant delays in treatment with epinephrine occurred in about one-third of cases in Denmark. 41 Per case mortality was estimated to be one in 26.6 cases in the UK for all causative drugs, 40 an outcome very similar to that observed in France for mortality related to NMBA anaphylaxis, 39 and that reported for all causative drugs in the US 42 and Japan. 27 A perioperative anaphylaxis mortality rate of 0e1.4% was recently reported for Western Australia (2000e2009).…”
Section: Incidence Causal Agents and Mortalitysupporting
confidence: 64%
“…This approach is required to avoid under-or overdosing epinephrine and fluid resuscitation. 40,41,63 We recommend that timely administration of epinephrine is required for Grade IIeIV reactions. However, we can only suggest initial doses for Grades II (20 mg) and III (50 mg) reactions.…”
Section: Epinephrine Dosingmentioning
confidence: 99%
“…These results are in accordance with a previous report. 7 These results demonstrated that the rescue therapy was suboptimal and/or delayed in at least 70% of the reported patients. In only 55% of cases was the administered epinephrine dose in accordance with the French recommendations (i.e.…”
mentioning
confidence: 85%
“…In one study, 45% of patients presented with grade III reactions (anaphylactic shock with circulatory instability) or grade IV reactions (cardiac arrest). 35 As life-threatening allergic reactions are seen as a relative contraindication to DPT by many allergists, this also presents an important barrier against performing DPT in perioperative allergy investigation.…”
Section: Barriers Against Provocation In Suspected Perioperative Allergymentioning
confidence: 99%